PENGARUH PERSEPSI WAJIB PAJAK ATAS PENERAPAN PERATURAN PEMERINTAH NOMOR 23 TAHUN 2018 DAN PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK USAHA MIKRO, KECIL, DAN MENENGAH DENGAN SOSIALISASI PERPAJAKAN SEBAGAI VARIABEL MODERASI - Rifki Syaputra (Jurnal Magister Akuntansi Trisakti, 2019)
AbstractThis study aims is to examine the effect of taxpayer perceptions about the implementation of Government Regulation 23 of 2018 (income tax on income received from or obtained by taxpayers who have certain gross circulation) and Taxation Understanding to Taxpayer Compliance with Micro, Small and Medium Enterprises (MSMEs) with Taxation Socialization as a Moderating Variable. Data is obtained from questionnaires filled by MSME respondents in Depok City in January 2019. A total of 95 questionnaires were returned with complete and manageable conditions. The analysis is done by multiple regression using the SPSS version 25.00 windows program. Hypothesis testing results show that Taxpayer Perception about the Implementation of Government Regulation 23 of 2018 and Taxation Understanding have a positive effect on MSME Taxpayer Compliance, Tax Socialization cannot strengthen Taxpayer Perception about the Implementation of Government Regulation 23 of 2018 to MSME Taxpayer Compliance, and Tax socialization cannot strengthen Taxation Understanding to MSME Taxpayer Compliance.